2016
DOI: 10.1080/07474938.2016.1140284
|View full text |Cite
|
Sign up to set email alerts
|

The “wrong skewness” problem in stochastic frontier models: A new approach

Abstract: Stochastic frontier models are widely used to measure, e.g., technical efficiencies of firms. The classical stochastic frontier model often suffers from the empirical artefact that the residuals of the production function may have a positive skewness, whereas a negative one is expected under the model, which leads to estimated full efficiencies of all firms. We propose a new approach to the problem by generalizing the distribution used for the inefficiency variable. This generalized stochastic frontier model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 18 publications
(34 reference statements)
0
19
0
1
Order By: Relevance
“…Lee (1993) showed that, in this case, the likelihood ratio statistic asymptotically follows a mixture of a χ 2 distribution with one degree of freedom and a point mass of 1/2 at zero. In the case of the extended model (5), Hafner et al (2016) show that, despite the fact that the information matrix is still singular at µ u = 0, the likelihood ratio statistic follows a standard χ 2 distribution because the parameter µ u is no longer on the boundary under the null hypothesis.…”
Section: Estimation and Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee (1993) showed that, in this case, the likelihood ratio statistic asymptotically follows a mixture of a χ 2 distribution with one degree of freedom and a point mass of 1/2 at zero. In the case of the extended model (5), Hafner et al (2016) show that, despite the fact that the information matrix is still singular at µ u = 0, the likelihood ratio statistic follows a standard χ 2 distribution because the parameter µ u is no longer on the boundary under the null hypothesis.…”
Section: Estimation and Evaluationmentioning
confidence: 99%
“…In practice, when the residuals have positive skewness, the maximum likelihood estimator will either fail to converge or will converge to a local maximum. A solution to this problem is proposed in Hafner et al (2016), which we adapt to our setting. We extend the distribution of u t to allow for negative values and extend its parameter µ u to lie in R. To be specific, when µ u < 0 we define the density of u t to be an exponential distribution mirrored onto the negative axis by reflecting it at zero.…”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this issue, several authors have proposed the use of distribution functions with negative asymmetry for inefficiency component. In partic-ular, Carree (2002) uses the Binomial probability function, Tsionas (2007) More recent attempts to obtain the desired direction of residual skewness are Feng et al (2013) where authors propose a finite sample adjustment to existing estimators and Hafner et al (2013) where authors use an artificial truncation.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that recent work has been attempting to overcome the datarelated issues when using stochastic frontier analysis to estimate the morning terminal vertex as well as the evening origin vertex (Hafner, et al, 2015;Almanidis and Sickles, 2012).…”
Section: Morning Terminal Vertex Modelmentioning
confidence: 99%